Post-TTM Rebound Pyrexia after Ischemia-Reperfusion Injury Results in Sterile Inflammation and Apoptosis in Cardiomyocytes - Tong, Giang; von Garlen, Nalina N. A.; Wowro, Sylvia J.; Lam, Phuong D.; Krech, Jana; Berger, Felix; Schmitt, Katharina R. L. (Mediators of Inflammation, 2019)
Introduction. Fever is frequently observed after acute ischemic events and is associated with poor outcome and higher mortality. Targeted temperature management (TTM) is recommended for neuroprotection in comatose cardiac arrest survivors, but pyrexia after rewarming is proven to be detrimental in clinical trials. However, the cellular mechanisms and kinetics of post-TTM rebound pyrexia remain to be elucidated. Therefore, we investigated the effects of cooling and post-TTM pyrexia on the inflammatory response and apoptosis in a cardiomyocyte ischemia-reperfusion (IR) injury model. Methods. HL-1 cardiomyocytes were divided into the following groups to investigate the effect of oxygen-glucose deprivation/reperfusion (OGD/R), hypothermia (33.5°C), and pyrexia (40°C): normoxia controls maintained at 37°C and warmed to 40°C, OGD/R groups maintained at 37°C and cooled to 33.5°C for 24 h with rewarming to 37°C, and OGD/R pyrexia groups further warmed from 37 to 40°C. Caspase-3 and RBM3 were assessed by Western blot and TNF-α, IL-6, IL-1β, SOCS3, iNOS, and RBM3 transcriptions by RT-qPCR. Results. OGD-induced oxidative stress (iNOS) in cardiomyocytes was attenuated post-TTM by cooling. Cytokine transcriptions were suppressed by OGD, while reperfusion induced significant TNF-α transcription that was exacerbated by cooling. Significant inductions of TNF-α, IL-6, IL-1β, and SOCS3 were observed in noncooled, but not in cooled and rewarmed, OGD/R-injured cardiomyocytes. Further warming to pyrexia induced a sterile inflammatory response in OGD/R-injured groups that was attenuated by previous cooling, but no inflammation was observed in pyrexic normoxia groups. Moreover, cytoprotective RBM3 expression was induced by cooling but suppressed by pyrexia, correlating with apoptotic caspase-3 activation. Conclusion. Our findings show that maintaining a period of post-TTM “therapeutic normothermia” is effective in preventing secondary apoptosis-driven myocardial cell death, thus minimizing the infarct area and further release of mediators of the innate sterile inflammatory response after acute IR injury.